Good Manufacturing Practices Evaluation in the Na Oogst Cigar Industry Center of Jember Regency: A Case Study of CV. Dwipa Nusantara Tobacco - Nanang Dwi Wahyono; Kurniawan Muhammad Nur; Mohammad Mirza Pratama; Dyah Kusuma Wardani; Aditya Wahyu Winadi Atmajaya; Fredy Eka Ardhi Pratama (Jurnal Manajemen Agribisnis dan Agroindustri, 2025)
Good Manufacturing Practices (GMP) are essential for maintaining product safety, hygiene, and consistency in the cigar manufacturing industry. This study evaluates the level of GMP compliance at CV. Dwipa Nusantara Tobacco, one of the key producers in the Na Oogst Cigar Industry Center of Jember Regency, and identifies areas requiring improvement to enhance product quality and competitiveness. Using a descriptive qualitative approach, data were collected through observations, interviews, and checklist assessments based on the Ministry of Industry Regulation No. 75/M-IND/PER/7/2010 and BPOM RI (2012). The evaluation identified three non-conformities-one minor related to inadequate handwashing facilities and two major involving the absence of laboratory testing for nicotine content and incomplete product labeling. The company achieved Level II GMP compliance, indicating that while most standards are met, several aspects still require corrective action. Recommended improvements include providing complete sanitation facilities, conducting regular laboratory nicotine analyses, and updating product labels to meet health regulation requirements. These measures are expected to strengthen GMP adherence, ensure consumer safety, and enhance the sustainability and reputation of the cigar industry in Jember Regency, a leading center for Na Oogst tobacco-based products.